The Profile of Cervical Cancer Patients at Soedarso Hospital - Sari Eka Pratiwi; Heru Fajar Trianto; Nabilah Nurul Fatinah; Muhammad In’am Ilmiawan; Iit Fitrianingrum; Desriani Lestari (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: The prevalence and mortality rates of cervical cancer differ by region with the highest rates found in Latin America, Southeast Asia, and Africa. In Indonesia, cervical cancer is the second-largest contributor to the latest cases in 2020. In West Kalimantan, over 20,000 women were diagnosed with cervical cancer in 2014. This study aims to describe the characteristics of cervical cancer patients in West Kalimantan. Methods: A descriptive observational study was conducted on patients from 2017 to 2019 according to the Soedarso Hospital database. All medical records were reviewed and analyzed to obtain the variable data; they were age, ethnics, origin, stage of cervical cancer, histopathology types, and hemoglobin (Hb) level. Results: Cervical cancer patients for the 2017–2019 period totaled 147 people with 30 deaths. In this study, 97 patients from 2017 to 2019 met the inclusion criteria. Cervical cancer was found from the age of 27 years with a peak at the age of 41–60 years. Most patients came from Pontianak and Kubu Raya cities (45.4% and 14.4%, respectively) with the most ethnic groups being Malays (41.2%). A total of 43.3% of patients had a parity amount of more than five times. Most patients came at stage IIIb (45.4%). The patients present with moderate to severe anemia with the lowest Hb level of around 2.3 g/dL. Based on histopathology, the type of squamous cell carcinoma ranks the highest (70.1%). Conclusions: Cervical cancer incidence reaches the peak at adults to elderly. The amount of parity seems to contribute to the incidence of cervical cancer in West Kalimantan. Most patients came at an advanced stage and the type of squamous cell carcinoma with moderate to severe anemia